Excessive EFHD1-dependent ER-mitochondrial contacts drive a maladaptive antiviral response in metabolic liver disease - David R. Eberhardt; Emma C. Rekate; Yasmin B. Masini; Hannah E. Duron; David Mollinedo; Adrian M. Velarde; Devorah Stucki; Tara R. Price; Sandra H.J. Lee; Enrique Balderas; Neeraj K. Rai; Ashley R. Bratt; et al. (Journal of Clinical Investigation, 2026)
Metabolic-associated steatohepatitis (MASH) involves hepatocyte damage that cannot be explained solely by lipid accumulation. Here, to discover injury-specific pathways, we focused on a gene of uncertain function, EF-Hand Domain Family Member D1 (EFHD1), identified in human genome-wide association studies of liver injury but not liver fat. We show that EFHD1, a Ca 2+ -dependent actin crosslinker, stabilizes endoplasmic reticulum–mitochondria contact sites (ERMCS), detecting spatiotemporal coincidence of inter-organellar proximity and ER Ca 2+ release. During MASH, EFHD1 upregulation drives pathological mitochondrial fragmentation via excessive contact persistence. This structural failure promotes mitochondrial double-stranded RNA escape and activation of a maladaptive antiviral PKR-associated stress response, a causal relationship also supported by Mendelian randomization in humans. Consequently, inhibiting EFHD1 in human and mouse models blunts hepatocyte damage. These findings identify EFHD1 as a Ca 2+ -dependent ERMCS stabilizer, reveal a hepatocyte-intrinsic injury pathway, and suggest EFHD1 inhibition as a therapeutic strategy.